Design of Website-Based Waste Management System using Laravel Framework in RT 06 Kramat Jati - Budi Eka Saputra; Isa (P3M Politeknik Negeri Bengkalis, 2025)
Waste management fees at the Neighbourhood Association level often experience obstacles such as recording errors, late payments, and a lack of information transparency. This has an impact on low service efficiency and citizen participation. The purpose of this research is to build a web-based information system that can support the waste management process, using the Laravel framework as the main tool to improve efficiency, transparency, and administrative accountability in RT 006 RW 010, Kramat Jati, East Jakarta. The study was conducted on 10 residents and RT administrators as respondents, selected based on their activity in every resident activity from February to May 2025. The system allows RT administrators to manage data digitally, while residents can monitor payment status in real-time. For residents who are not familiar with technology, admins can enter data manually. The test results show that all features in the system run smoothly and support the administration process effectively. This system has been proven to significantly reduce manual recording and recap time, as well as increase citizen involvement in the payment process. In the future, this system has the potential to be further developed with the integration of digital payments such as QRIS and mobile applications, to expand reach and improve service convenience